Building digital marketing program for Abera brand product line of Khai Hoan Net Joint Stock Company - Ton, Nu Thuc Quyen (Vietnam-Korea University of Information and Communication Technology, 2024)
Bachelor thesis of Business Administration - Digital Marketing